2022
DOI: 10.3389/fmicb.2022.1004589
|View full text |Cite
|
Sign up to set email alerts
|

Electron shuttles enhanced the removal of antibiotics and antibiotic resistance genes in anaerobic systems: A review

Abstract: The environmental and epidemiological problems caused by antibiotics and antibiotic resistance genes have attracted a lot of attention. The use of electron shuttles based on enhanced extracellular electron transfer for anaerobic biological treatment to remove widespread antibiotics and antibiotic resistance genes efficiently from wastewater or organic solid waste is a promising technology. This paper reviewed the development of electron shuttles, described the mechanism of action of different electron shuttles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 148 publications
0
2
0
Order By: Relevance
“…Zhang et al showed that the improvement in AD performance was primarily attributed to the enhancement of the DIET process by nano-magnetite to facilitate the syntrophic metabolism of organic matter [48]. However, carbon-based nanomaterials are usually prone to wash away and are difficult to recycle, while metal-based nanomaterials possibly result in material agglomeration, leading to a significant reduction in utilization efficiency [49][50][51]. Simultaneously, both the toxicity effect of nanoparticles on microorganisms and the high cost of nanomaterials hinder its application [52].…”
Section: The Evolution Of the Dietmentioning
confidence: 99%
“…Zhang et al showed that the improvement in AD performance was primarily attributed to the enhancement of the DIET process by nano-magnetite to facilitate the syntrophic metabolism of organic matter [48]. However, carbon-based nanomaterials are usually prone to wash away and are difficult to recycle, while metal-based nanomaterials possibly result in material agglomeration, leading to a significant reduction in utilization efficiency [49][50][51]. Simultaneously, both the toxicity effect of nanoparticles on microorganisms and the high cost of nanomaterials hinder its application [52].…”
Section: The Evolution Of the Dietmentioning
confidence: 99%
“…However, several artificial shuttles including chemicals, metals and carbon-based materials aid in degrading antibiotics and several ARG containing plasmids, mobile elements after lysing the bacterial cells. Carbon nanotubes, graphene oxide, are carbon based nanomaterials that can act as electron shuttles and reduce ARGs and HGT in anaerobic degradations [47]. Another graphene compound graphitic carbon nitride can be used for reducing micropollutants and ARG containing bacteria [48].…”
Section: Processes/treatments That Can Reduce Argsmentioning
confidence: 99%